BER and Availability Measured on FSO Link - Kvicala, Radek; Kvicera, Vaclav; Grabner, Martin; Fiser, Ondrej (Radioengineering Society, 2007)
The BER and the availability belong among the basic qualitative parameters of free space optical (FSO) links. The BER parameter is usually mentioned by FSO manufacturers, but it is not defined what conditions a certain value of BER stands for. This article deals with problems of measuring the BER of free space optical link and with questions how to determine the probability of unavailability of a certain link. The implementation of bit error rate tester with the E1 interface system is presented. In the article the statistics of the meteorological optical range for the year 2006 are shown. Using these data one can determine the probability of a certain value of atmospheric attenuation that influences the link unavailability.
Keywords: Free space optical link; quality of service; meteorological optical range; link unavailability; bit error rate